Mundos híbridos : um estudo das imaginações geográficas contemporâneas - Nascimento, Gabriel Vidal (2024)
How we imagine the world geographically matters. Geographical imaginations (Massey, 2008, 2017) shape our cosmopolitical relationships with human and non-human beings. Western capitalist modernity has produced a geographical way of imagining the world based on the antagonistic society/nature dualism, which is implicated in the contemporary environmental and civilizational crisis. However, the ecological and political events that occurred, especially from the second half of the 20th century, explicitly and dramatically questioned this separation and denounced the violent practices involved in this abyss between society and nature. In this context, space was opened for the constitution of a hybrid geographic imagination that conceives a world formed from the inseparable composition of humans and non-humans, or even, in another formula, the hybridization of nature and society (culture). The central aim of this research is to reflect on this geographical imagination from environmental issues. We also aim to contribute to its theoretical outline based on a relational conception of environments as interactive compositions of human and non-human devices and artisans on multiple scales.